Комплексная оценка эффективности санаторного лечения туберкулеза у детей - Елена Юрьевна Власова; Марина Эдуардовна Лозовская; Геннадий Геннадьевич Карасев; Юлия Анатольевна Яровая; Ксения Павловна Юлина; Анна Романовна Сапожникова (Medicine and health care organization, 2026)
Введение. Санаторный этап является важным компонентом комплексной терапии и реабилитации детей, больных туберкулезом, и лиц из групп риска. Для оценки его эффективности необходим системный подход, учитывающий динамику совокупности клинико-функциональных показателей. Цель исследования. На базе ФГБУ «Детский туберкулезный санаторий “Пушкинский”» Минздрава России (ДТС) провести апробацию комплексной оценочной таблицы для определения эффективности санаторного этапа лечения, разработанную совместно кафедрой фтизиатрии ФГБОУ ВО СПб ГПМУ Минздрава России и ФГБУ ДТС «Пушкинский» Минздрава России. Материалы и методы. Проведены анализ медицинских карт пациентов, проходивших реабилитацию в санатории с диагнозами «туберкулез органов дыхания» и «латентная туберкулезная инфекция», оценка эффективности лечения с помощью специальной таблицы, где ключевые показатели оценивались в баллах при поступлении и выписке. В результате высчитывался коэффициент эффективности: частное от деления суммы баллов при поступлении на сумму баллов при выписке. Лечение включало медикаментозные (химиотерапия) и немедикаментозные (галотерапия, ионотерапия, лечебная физкультура, массаж, физиотерапия) методы. Результаты. Использование оценочной таблицы позволило стандартизировать оценку результатов лечения. На основе коэффициента эффективности были выделены четыре категории результатов: «значительное улучшение», «улучшение», «без перемен» и «ухудшение». Анализ показал положительную динамику большинства оцениваемых параметров у пациентов обеих групп. Introduction. The sanatorium stage is an important component of the comprehensive therapy and rehabilitation of children with tuberculosis and individuals from risk groups. To evaluate its effectiveness, a systematic approach is required that takes into account the dynamics of a set of clinical and functional indicators. The aim of the research — to test a comprehensive assessment table for determining the effectiveness of the sanatorium stage of treatment at the Federal State Budgetary Institution Children's Tuberculosis Sanatorium "Pushkinsky" of the Ministry of Health of Russia (DTS). This table was developed jointly by the Department of Phthisiology of the Federal State Budgetary Educational Institution of Higher Education Saint Petersburg State Pediatric Medical University and the Federal State Budgetary Institution DTS “Pushkinsky” of the Ministry of Health of Russia. Materials and methods. Analysis of medical records of patients undergoing rehabilitation at the sanatorium with diagnoses of “respiratory tuberculosis” and “latent tuberculosis infection” was carried out, and treatment effectiveness was assessed using a special table, where key indicators were assessed in points upon admission and discharge. As a result, the effectiveness coefficient was calculated: the quotient of the sum of points upon admission divided by the sum of points upon discharge. Treatment included medication (chemotherapy) and non-medication methods (halotherapy, ionotherapy, exercise therapy, massage, and physical therapy). Results. The use of an assessment table allowed for standardized assessment of treatment outcomes. Based on the effectiveness coefficient, four outcome categories were identified: “significant improvement”, “improvement”, “unchanged”, and “worsening” The analysis revealed positive dynamics in most of the assessed parameters in patients in both groups.